Emotional intelligence in the initial teacher training (2019)
The objective of the article is to evaluate emotional intelligence in the initial teacher training of the mathematics bachelor program at the "Universidad Francisco de Paula Santander", San José de Cúcuta, Colombia. The methodology is framed in the qualitative approach with some complementary aspects of the quantitative approach, the applied technique is the interview and the trait meta-mood scale instrument. The results describe that the impacts of integrating the emotive dimension in the learning strategies of mathematics is a greater resilience in the teachers in formation, since thanks to the contact with their emotions through introspection and reflection they manage to draw plans and alternatives that help them to devote more time, ask more and study better, especially in those aspects that cause them difficulty.